LANGUAGE IN COURTROOM DISCOURSE - Susanto SUSANTO (International Conference on Education and Language (ICEL), 2016)
Courtroom discourse, which is in the field of Forensic Linguistics, presents the analysis on legal language used in the courtroom settings (Coulthard & Johnson, 2007; Olsson, 2004; Wang, 2012). It mainly focuses on the legal language as object, process and instrument (Stygall, 1994); and the legal language in enabling and reporting contexts (Matthiessen, 2009). In the paper, I present an overview of some critical issues concerning with the studies of courtroom language. By taking a case study of a Chinese criminal trial, I exemplify some language aspects used in the courtroom to shed light on the nature of the courtroom discourse - the primary speaking roles of a judge in directing, ruling and instructing. Further, I explore the distribution of information in the judge’s speech realized by the tone groups.